Association of Social Disconnection With the Incidence and Prognosis of Atrial Fibrillation: A Multistate Analysis - Yu Qiao; Yuyang Wang; Tingting Ge; Yahong Liu; Yuzhu Chen; Guodong Niu; Yifang Yuan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Social disconnection, including loneliness and social isolation, is associated with increased morbidity and death. However, its impact on the incidence and prognosis of atrial fibrillation (AF) remains inconclusive. Methods and Results The present prospective cohort study enrolled 418 656 participants without AF and cardiovascular disease from the UK Biobank. A loneliness scale was constructed with 2 domains (loneliness feeling, inability to confide) and social isolation scale was constructed with 3 domains (living alone, lack of social support, and lack of social activity). We used a multistate model to analyze the impacts of the 2 scales on the progression from baseline to incident AF and subsequent major adverse cardiovascular events and further to death. Over a median follow‐up of 14.7 years, 25 539 participants developed incident AF, among whom 7283 developed incident major adverse cardiovascular events, and 5165 died. Social isolation and loneliness scales were associated with both a higher incidence and worse prognosis of AF, with hazard ratios per 1‐point increase of 1.06 (95% CI, 1.04–1.09) for the loneliness scale and 1.03 (95% CI, 1.02–1.05) for the social isolation scale for incident AF, and 1.12 to 1.14 for the loneliness scale (all P<0.001) and 1.12 to 1.27 for the social isolation scale (all P<0.001) after AF development. Loneliness feeling and living alone may be important contributors. Conclusions Loneliness and social isolation were both associated with a higher incidence and a worse prognosis of AF but to different extents. These observations highlight the importance of integrating social connection into the prevention and management of AF.